China's new role in African politics from non-intervention towards stabilization? - Hartmann, Christof 1967-; Noesselt, Nele (Routledge,Taylor & Francis Group, 2021)
"China's rise to global power status in recent decades has been accompanied with a deepening trade relationship with Africa, leading to much academic debate about the influence of Chinese business in the continent. However, China's engagement with African states at the political and diplomatic level has received less attention in the literature. This book investigates the impact of Chinese policies on African politics, asking how China deals with political instability in Africa and in turn how Africans perceive China to be helping or hindering political stability. Whilst China officially operates with a foreign policy strategy which conceives of Africa as one integrated monolithic area (with FOCAC the flagship of inter-continental cooperation), this book highlights the plurality of context-specific interaction patterns between China and African elites, demonstrating how Chinese politics in the context of resource-rich and geostrategically important countries differs from the strategies coined for relations with those African states without strategic resources. By looking comparatively at a range of different country cases, the book aims to develop a theoretical framework that assesses how China reacts to political stability and instability, and in which ways the country contributes to domestic political dynamics and stability within African states. China's New Role in African Politics will be of interest to researchers from across Political Science, International Relations, International Law and Economy, Security Studies, and African and Chinese Studies"--
Keywords: Internationale Politik; Politische Stabilität; Afrika; China; Africa, Sub-Saharan / Foreign relations / China; Africa, Sub-Saharan / Politics and government / 21st century; China / Politics and government / 21st century; China / Foreign relations / Africa, Sub-Saharan; Diplomatic relations; Politics and government; Sub-Saharan Africa; 2000-2099; Aufsatzsammlung